How Intensive Short-Term Dynamic Psychotherapy Merges with Hypnotism and Solution- Focused Methods - Darvishzadeh Nooshabadi Golnaz (Journal of Alternative Medicine and Mind Body Practices, 2025)
Intensive Short-Term Dynamic Psychotherapy (ISTDP) has proven effective in over 120 outcome studies, particularly for anxiety, depression, and personality disorders. This conceptual paper proposes a theoretical integration of ISTDP with Solution- Focused Brief Therapy (SFBT) and clinical hypnosis. Each modality offers unique strengths—ISTDP enables rapid emotional processing, SFBT builds client resilience and solutions, and hypnosis enhances neuroplasticity and emotional receptivity. Drawing on existing empirical and neuroscientific literature, this paper synthesizes these modalities into a unified clinical framework. The integrated model emphasizes accelerated change through emotional access, strategic future orientation, and unconscious facilitation. Case examples illustrate the framework's practical applications across complex clinical presentations. The integration addresses gaps in single-modality treatments and provides a cost-effective, neurobiologically supported method of intervention. This article offers clinicians structured decision- making strategies and practical tools for real-time integration, while outlining future directions for empirical research.
Keywords: Intensive Short-Term Dynamic Psychotherapy (ISTDP)